1985
DOI: 10.1083/jcb.101.4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of high density lipoprotein by chicken liver: intracellular transport and proteolytic processing of nascent apolipoprotein A-1.

Abstract: To study the in vivo processing and secretion of Apolipoprotein A-I (Apo A-I), young chickens were administered individual L-[3H]amino acids intravenously and the time of intracellular transport of nascent Apo A-I from rough endoplasmic reticulum (RER) to the Golgi apparatus was measured. Within 3 to 9 min there was maximal incorporation of radioactivity into Apo A-I in both the RER and the Golgi cell fractions. By contrast, the majority of radioactive albumin was also present in the RER by 3 to 9 min, but did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…These observations correlate with results of a study on chicken hepatocytes, 53 which concluded that apo A-l is synthesized in the ER, transported to the Golgi very rapidly, and remains there for a longer period before secretion into the blood.…”
supporting
confidence: 79%
“…These observations correlate with results of a study on chicken hepatocytes, 53 which concluded that apo A-l is synthesized in the ER, transported to the Golgi very rapidly, and remains there for a longer period before secretion into the blood.…”
supporting
confidence: 79%
“…A similar cleavage site, GlnHis, is present in chicken apoAI (40). More than 90% of the apoAI in chicken plasma is cleaved which demonstrates that the proteolytic machinery is operational in chickens (31).…”
Section: Discussionmentioning
confidence: 93%
“…Whereas VLDL particles have been readily isolated from the Golgi (9, 10), efforts to identify HDL particles along the secretory pathway have had little success (9). Although these findings provided little support for the intracellular assembly of nascent HDL, a number of other studies supported the concept of an intracellular apoA-I lipidation pathway (11)(12)(13)(14)(15)(16). With the discovery of the ABCA1 transporter, many of these concepts concerning nascent HDL assembly have been revised, and recent studies support the idea of both ABCA1-dependent and -independent mechanisms responsible for apoA-I lipidation (17,18).…”
mentioning
confidence: 99%